Borrowing to Keep Up (with the Joneses) : Inequality, Debt, and Conspicuous Consumption - Banuri, Sheheryar; Nguyen, Ha (World Bank, Washington, DC, 2020)
The quest for status is a powerful motivator, but does it affect inequality? This paper presents a novel lab experiment that was designed and conducted to identify the relationship between inequality, status signaling, debt, and conspicuous consumption. It reports three main findings: First, consumption increases when it is "conspicuous" (i.e. is both observable, and signals ability/status). Second, borrowing increases when consumption is conspicuous. More critically, this increase in loan-taking is driven by those at the bottom of the income distribution. Third, in the presence of conspicuous consumption, access to finance exacerbates inequality. The results point to a vicious cycle of inequality and costly borrowing.